Elastic Search AI in Enterprise Systems: Revolutionizing Universities and Health Institutions - Gaurav Krishan Ohri, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article explores the revolutionary impact of ElasticSearch AI in transforming data management and operational efficiency within universities and healthcare institutions. The article examines how this technology addresses critical challenges in data volume management, regulatory compliance, and operational effectiveness across these sectors. Through comprehensive article analysis, the research demonstrates how Elastic Search AI's advanced search, analytics, and security capabilities have fundamentally altered how institutions handle information and make decisions. The article covers the technology's implementation across various domains, from administrative functions to research capabilities, highlighting its role in enhancing user experiences and institutional effectiveness. By examining specific applications in both educational and healthcare settings, the study reveals how ElasticSearch AI enables personalized learning environments, streamlined administrative processes, and improved healthcare delivery systems. The article also provides detailed implementation guidelines, emphasizing the importance of strategic planning, security measures, and system maintenance in achieving optimal results. This article contributes to understanding how artificial intelligence and search technologies can be effectively deployed to address complex institutional challenges while maintaining security and efficiency.
Keywords: ElasticSearch AI; Enterprise Systems; Healthcare Informatics; Educational Technology; Data Management